2014
DOI: 10.1186/1758-5996-6-28
|View full text |Cite
|
Sign up to set email alerts
|

Immune-inflammatory markers and arterial stiffness indexes in subjects with acute ischemic stroke with and without metabolic syndrome

Abstract: Objective: The aim of our study was to evaluate the associations between arterial stiffness indexes and immune-inflammatory markers in subjects with acute ischemic stroke with and without metabolic syndrome. Materials/Methods: We enrolled 130 patients with acute ischemic stroke and metabolic syndrome, 127 patients with acute ischemic stroke without metabolic syndrome and 120 control subjects without acute stroke. Applanation tonometry was used to record the augmentation index (Aix) and pulse wave velocity (PWV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 35 publications
1
42
1
1
Order By: Relevance
“…Therefore, the key clinical question is whether the incidence of cardiovascular events in these patients is mainly due to early atherosclerosis per se (increasing of all stiffness parameters) or to persistent inflammation, which could contribute to the atherosclerotic process through the maintenance of endothelial dysfunction. Indeed, IBD patients are carriers of a significant inflammatory background, as shown by altered level of CRP, and the pivotal role of inflammation in the onset of atherosclerosis has been confirmed by previous studies, and has been also correlated with the level of proinflammatory cytokines [36,37]. In addition, it has been also reported that high levels of such cytokines, selectins and adhesion molecules were strongly related to the "markers" of arterial stiffness in patients suffering from cerebrovascular events [37,38].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, the key clinical question is whether the incidence of cardiovascular events in these patients is mainly due to early atherosclerosis per se (increasing of all stiffness parameters) or to persistent inflammation, which could contribute to the atherosclerotic process through the maintenance of endothelial dysfunction. Indeed, IBD patients are carriers of a significant inflammatory background, as shown by altered level of CRP, and the pivotal role of inflammation in the onset of atherosclerosis has been confirmed by previous studies, and has been also correlated with the level of proinflammatory cytokines [36,37]. In addition, it has been also reported that high levels of such cytokines, selectins and adhesion molecules were strongly related to the "markers" of arterial stiffness in patients suffering from cerebrovascular events [37,38].…”
Section: Discussionmentioning
confidence: 57%
“…On the basis of the collected data, an averaged radial pressure waveform was generated and a corresponding aortic pressure waveform and blood pressure calculated by the validated transfer function. The aortic pressure waveform was used to calculate the Aortic AIx (difference in height between the first (P1) and second (P2) systolic peaks expressed as a percentage of pulse pressure (PP) [36]). …”
Section: Pulse Wave Analysismentioning
confidence: 99%
“…Thus inflammation marker evaluation has in DFS multiple points of potential importance concerning a better evaluation and analysis of these crucial key points: (1) pathogenetic role in ulcers and their micro and macrovascular background; (2)possible link between inflammation state and adipo-metabolic axis; (3) predictive role towards foot complications such as ulcers incidence; (4) putative role as markers of gravity of wounds and ulcers in a diabetic foot; (5) association with cardiovascular co-morbidity (prevalent and incident) in subjects with DFS; (6) prognostic role towards ulcer healing; (7) strict association with peripheral artery comorbidity (PAD); and (8) pathogentic links with metabolic syndrome and NASH [93][94][95][96][97][98][99] . It explains that a strict and prospective inflammation marker evaluation could be useful in practical management of foot complications in diabetic subjects in every medical setting (Internal Medicine, Diabetology, Surgery, Orthopedics) to better evaluate a complex disease such as DFS in a multispecialistic management contest.…”
Section: Resultsmentioning
confidence: 99%
“…The level of systemic inflammation in stroke patients strongly depends on the diagnostic subtype of stroke and is directly related to the extent of the neurological damage during the acute phase and to the residual disability (95)(96)(97)(98)(99)(100)(101).…”
Section: Cerebrovascular Diseasementioning
confidence: 99%